CMS systems in rapeseed and their use in the breeding of domestic hybrids - I. N. Anisimova (Труды по прикладной ботанике, генетике и селекции, 2020)
Development of heterotic hybrids is the most efficient approach to solve the problem of increasing the yield of rapeseed (Brassica napus L.), a leading oilseed crop. The cytoplasmic male sterility (CMS), widely used in rapeseed hybrid seed production, makes it possible to control hybridization between female and male lines. A review of publications on the nature of CMS systems in rapeseed and their utilization in breeding is presented. In rapeseed there are more than 10 known CMS systems of alloplasmic and homoplasmic origin. The male sterility character proved to be determined by chimeric mitochondrial genes, characterized by the presence of novel transcribed open reading frames (orf). Mitochondrial CMS genes associated with nap, pol, ogu and Nsa sterility types as well as nuclear Rf genes for pollen fertility restoration were identified. Molecular marker systems for identification of CMS-inducing and male fertility restoring genes were developed. The ogu, pol, MSL and inap CMS systems are commonly used for producing industrial rapeseed hybrids. The State Register of the Russian Federation for 2019 contains rapeseed hybrids of only foreign origin. Main achievements in domestic rapeseed hybrid production are highlighted. Research and breeding institutions developed new source material for rapeseed hete rotic hybrid breeding in various regions of the country. The sterility and fertility restoration sources were received from Canadian and French institutions as well as from domestic working collections. The yield structure traits did not deteriorate after transferring hybrid maternal lines to the sterile cytoplasm, while the glucosinolate content increased when pollen fertility restoring genes were transferred into paternal lines. Dihaploid (androclinium) lines and in vitro culture of unfertilized ovules were used to accelerate the breeding process. Experimental hybrids were developed using pol and ogu CMS.